Lessons from the Auriga discs: the hunt for the Milky Way's ex-situ disc is not yet over - Gómez, Facundo A.; Grand, Robert J. J.; Bustamente, Sebastian; Pakmor, Rüdiger; Springel, Volker (Arxiv, 2017)
We characterize the contribution from accreted material to the galactic discs of the Auriga Project, a set of high resolution magnetohydrodynamic cosmological simulations of late-type galaxies performed with the moving-mesh code AREPO. Our goal is to explore whether a significant accreted (or ex-situ) stellar component in the Milky Way disc could be hidden within the near-circular orbit population, which is strongly dominated by stars born in-situ. One third of our models shows a significant ex-situ disc but this fraction would be larger if constraints on orbital circularity were relaxed. Most of the ex-situ material ($\gtrsim 50%$) comes from single massive satellites ($> 6 × 10^{10}~M_{\odot}$). These satellites are accreted with a wide range of infall times and inclination angles (up to $85^{°}$). Ex-situ discs are thicker, older and more metal-poor than their in-situ counterparts. They show a flat median age profile, which differs from the negative gradient observed in the in-situ component. As a result, the likelihood of identifying an ex-situ disc in samples of old stars on near-circular orbits increases towards the outskirts of the disc. We show three examples that, in addition to ex-situ discs, have a strongly rotating dark matter component. Interestingly, two of these ex-situ stellar discs show an orbital circularity distribution that is consistent with that of the in-situ disc. Thus, they would not be detected in typical kinematic studies.
Gesehen am 11.11.2023